On a property of the Nevanlinna characteristic - Zabolotskyy, M. V.; Zabolotskyy , T. M. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.53 We prove the existience of entire functions f of an arbitrary lower order λ0 and the order ρ=λ+1 such that equation* r → +∞T(r + 1, f)/T(r, f) > 1. equation* Obtained results show that the condition ρ - λ < 1 of Valiron’s theorem can not be improved.